Modern Libya Magazine and its Position on Women's Issues (1963-1969)AD (Journal of Human Sciences, 2024)
“Modern Libya” magazine kept up with its coverage of many issues related to Libyan women. It is a bi-monthly illustrated magazine that began publication in 1963 AD. Due to its commitment to political, intellectual, literary and artistic issues in general, it paid special attention to Libyan women’s issues, as it followed their most important political, social and cultural activities The aim of the magazine's administration was to pay attention to women's issues, to publish their news through some articles, or to quote some excerpts from other newspapers, to highlight the role of women and the concepts related to their rights in education, social participation, holding public positions, choosing a husband, maternity care, etc. through the magazine as cultural and educational media. Its entertainment has a significant impact on the trends of public opinion and establishing awareness in society. Despite the lack of media space devoted to women, “Modern Libya” provided us with important basic issues related to women, examining their affairs and problems and finding solutions for them.  The researcher will analyze women's issues in the magazine "Modern Libya" from 1963 - 1969 AD, during which she will go through many occasions and events related to the topic of women.